Angular correction related to excision of specific cords in fasciectomy for Dupuytren's disease. (June 2014) - Trickett, R. W.; Savage, R.; Logan, A. J.
Named cords were excised sequentially at fasciectomy for Dupuytren's disease and the resultant correction in the joint angle was measured intra-operatively in 99 fingers. Eighty-two metacarpophalangeal and 59 proximal interphalangeal joints were affected. At the metacarpophalangeal joint, excision of the central cord resulted in 82% correction in 69 joints, and spiral/lateral cord excision resulted in an additional 12% correction in 10 joints. At the proximal interphalangeal joint, excision of the central cord resulted in 44% correction in 36 joints, spiral/lateral cord excision resulted in an additional 19% correction in 16 joints, and retrovascular cord excision resulted in a further 23% correction in 27 joints. Subsequent division of the accessory collateral ligament resulted in a further 14% correction in 14 joints. Larger pre-operative angles of the proximal interphalangeal joint were associated with a retrovascular cord, and larger combined angles were associated with an increasing number of pathological structures involved. The data explain the complexity of surgery at the proximal interphalangeal joint, where four structures are implicated in causing flexion deformity.